Green ship recycle yard design - Sunaryo, Sunaryo; Pahalatua, Dovan (Journal of Naval Architecture and Marine Engineering, 2015)
The life cycle of a ship has an age limit related to its operation. When the ship economically is not profitable any more, it will be recycled or scrapped. Since the scrapped ship has plenty of hazardous materials, special care should be carried out to manage the wastes in accordance with the national and international available regulations. With regard to this a ship recycle yard that conducts ship breaking and recycle of the ships outfits, machineries, and infrastructure should be well designed in order to comply to all regulations that prevent it from producing harmful and polluting wastes to human and environment. The study was aimed to design an environmentally friendly or green ship recycle yard in Indonesia as a pilot project in anticipation to the booming of old used merchant ships fleet due to the implementation of cabotage principle. The project is located in the Maritime Industrial Cluster in Tanggamus Regency, Lampung Province, Sumatera. The ship recycle yard is designed with a capacity of maximum 30,000 DWT ship to be recycled, and all the activities involve in the yard would comply and refer to the environmental and IMO regulations, to ensure that no harm and hazardous wastes polluting the surrounding land and sea by arranging a proper layout and providing proper facilities and working procedures.